Pemberdayaan Santri untuk Kemandirian Keuangan Ponpes melalui Fundraising & Pelatihan E-commerce - Puji Hadiyati; Wiwiek Prihandini; Reny Fitriana Kaban (FEB-UP Press, 2020)
Empowerment for orphan and poor students in Islamic Boarding School Hidayatulah at Bojongilir, Bogor needs to be done by Community Engagement team of Perbanas Institute. This effort has been done by fundraising and e-commerce training in order to create financial independence of the boarding school. The methode for the fundraising is as follows: 1). Collect data on the needs of boarding schools and the students, namely personal computers (PCs) and 200 portable tables for learning process. 2).Look for funding sources from outside the campus to improve the procurement of these stuffs. 3). Submit the community engagement proposals to Corporate Social Responsibility (CSR) of PT Waskita Karya and HIbah Ristek Dikti Program 2018. While provide assistance in e-commerce training is to support entrepreneurial activities, such as raising patin/ tilapia/catfish and making dried potatoes in packs in order to be marketed in modern way. The training was given in two stages with material themes â€œDigital Entrepreneur in the Industrial Age 4.0 For Studentsâ€ and â€œHow to Transact in E-commerceâ€. Before and after training the participants were given a test to determine the level of knowledge about e-commerce. At the end of the training a satisfaction survey was conducted on the training for the participants. This training has a positive impact on increasing the digital marketing motivation, knowledge and skills of the students.